GSK‐3β inhibition protects the rat heart from the lipopolysaccharide‐induced inflammation injury via suppressing FOXO3A activity. Issue 11 (10th September 2019) - Li, Zhigang; Zhu, Huifang; Liu, Chang; Wang, Yumei; Wang, Duo; Liu, Huan; Cao, Wenze; Hu, Yi; Lin, Qin; Tong, Chang; Lu, Min; Sachinidis, Agapios; et al.
Abstract: Sepsis‐induced cardiac dysfunction represents a main cause of death in intensive care units. Previous studies have indicated that GSK‐3β is involved in the modulation of sepsis. However, the signalling details of GSK‐3β regulation in endotoxin lipopolysaccharide (LPS)‐induced septic myocardial dysfunction are still unclear. Here, based on the rat septic myocardial injury model, we found that LPS could induce GSK‐3β phosphorylation at its active site (Y216) and up‐regulate FOXO3A level in primary cardiomyocytes. The FOXO3A expression was significantly reduced by GSK‐3β inhibitors and further reversed through β‐catenin knock‐down. This pharmacological inhibition of GSK‐3β attenuated the LPS‐induced cell injury via mediating β‐catenin signalling, which could be abolished by FOXO3A activation. In vivo, GSK‐3β suppression consistently improved cardiac function and relieved heart injury induced by LPS. In addition, the increase in inflammatory cytokines in LPS‐induced model was also blocked by inhibition of GSK‐3β, which curbed both ERK and NF‐κB pathways, and suppressed cardiomyocyte apoptosis via activating the AMP‐activated protein kinase (AMPK). Our results demonstrate that GSK‐3β inhibition attenuates myocardial injury induced by endotoxin that mediates the activation of FOXO3A, which suggests a potential target for the therapy of septic cardiac dysfunction.